Emergence of OXA-48 Carbapenemase Producing Klebsiella pneumoniae in a Neonatal Intensive Care Unit in Marrakech, Morocco. (March 2019) - Taoufik, Lahoucine; Amrani Hanchi, Asma; Fatiha, Bennaoui; Nissrine, Slitine; Mrabih Rabou, Maouainine Fadl; Nabila, Soraa
Goal: This work aims to describe and explore the circumstances of appearance of Klebsiella pneumoniae producing OXA-48 carbapenemase, which has occurred in a neonatal intensive care service at the Mohammed VI University Hospital of Marrakech. Results: During February 2015, the alert was triggered by the isolation of 6 isolates of K pneumoniae with the same antibiotic susceptibility profile in the neonatal intensive care service, suggesting a possible outbreak. Blood cultures represented the main site of isolation of these isolates. The phenotypic study of the isolates made it possible to identify a strain of K pneumoniae susceptible to third-generation cephalosporins, ciprofloxacin, and aminoglycosides, and resistant to ertapenem, β-lactamases inhibitors (ticarcillin-clavulanate, piperacillin-tazobactam; amoxicillin-clavulanic acid), and cotrimoxazole. The genotypic study of the epidemic isolate revealed the presence of the blaOXA-48 gene. The action to be taken was the establishment of corrective measures to stop this epidemic to a multi-resistant germ transmitted by hand transmission. The reinforcement of hygiene measures and the awareness of the staff made it possible to put an end to the epidemic at March 30, 2015, without closing the service. The outcome of 6 infected newborns was fatal due to the fragile terrain and the inappropriate probabilistic antibiotic therapy. Conclusion: The production of carbapenemase in K pneumoniae is an emerging resistance mechanism that must be suspected and identified to offer targeted therapy and to limit its spread. The implementation of a local policy to control multidrug-resistant germs is essential to limit their dissemination in hospitals.